Borneo X Track - Salim, Azzatul Fatonah; Arbain, Aman Shah; Ismail, Mariam Hanani; Salpau, Mohammad Shazwan; Fattin, Nurul Afiqah (2013)
The name of our company is Borneo X Track. Motocross is one of the developing extreme sports in Malaysia. Motorcycle enthusiasts are taking the nation's speedways and race tracks in the ever increasing numbers to experience the full potential of their vehicles in a safe, controlled and dedicated environment. The majority of these people are neither professional nor amateur racers who seek the safety and controlled conditions offered by dedicated track venues. Thus, our company helps these seekers to find that perfect track for them to show off their talented skills. Our track is the first dirt-type motocross track in Malaysia that offers 3 track trails which is freestyle, endurocross, and supercross. We are emphasizing on these 3 types of racing based on the needs and the current market of tracks business. However, there are many future development ideas such as hill-climb motocross course and other types of vehicles (All terrain vehicles & bicycle motocross) that can be implemented after our company is stable and fully establish. This shows how motorsports and track industries in Malaysia have a huge market offering range of future opportunity. Our company is basically operating in two separate venues where our headquarters (main office) is located in the capital city of Sabah, Kota Kinabalu and our track is located in Sandakan, Sabah. The size of our land where our track will be located is 13.13 acres. The land is a former palm oil nursery. Taking the advantages to our side, the palm oil trees planted on the compound ease our track building and modification process. This is because; these trees will covers our budgeting on building concrete walls to make our track soundproof. We expect to start our services to public by January 2014. There are 5 proposed courses that can be done in our track which is motorsports seminar, motocross practical courses, domestic tournament, international tournament, or track rental. Included in our courses are guaranteed safety, high quality equipments, and excellent service which will make every customer return to carve extreme experience into their memories. Total capital to deliver these facilities is RM426,666 where every partner in Borneo X Track are required to pay RM85,333.20 each to have equal shares on the company.